If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8(1 + -6x) + 2 = 346 (1 * 8 + -6x * 8) + 2 = 346 (8 + -48x) + 2 = 346 Reorder the terms: 8 + 2 + -48x = 346 Combine like terms: 8 + 2 = 10 10 + -48x = 346 Solving 10 + -48x = 346 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + -48x = 346 + -10 Combine like terms: 10 + -10 = 0 0 + -48x = 346 + -10 -48x = 346 + -10 Combine like terms: 346 + -10 = 336 -48x = 336 Divide each side by '-48'. x = -7 Simplifying x = -7
| 4x+10+3x+6=180 | | 135/105 | | 81/(-9) | | -4-3n+3=23 | | x=218+508 | | 3.6/y=10.8/12 | | 30.99-25= | | 5(8x-8)=440 | | 11-8x=1-6x | | 3(5y-4)+15=5(y-3)-(3y+2) | | 12+3x=24-3x | | -20m+20=-17m-13 | | 20=12x+3 | | 5/6=x/6 | | 9x+(-7)=8x | | 10c=-11-3(-3c+1) | | -8r=-3r+20 | | x/6=0,5 | | 14v-12+7w+(-4v)= | | 20-y+20=2y-20 | | 6-0.5x=15 | | 9x+(17)=8x | | 8h+8=4h | | 18.75=3u | | 459.90=210x+1.19x | | 4=29+13x | | 6c=-8+2c | | -16-6-2g=-4(-g-20) | | y+3y-1=y | | -3g+4=9-8g | | 7x-x-10=-4 | | F(-4)=3x^2+5 |